Thermo-Economic Evaluation of the Combined Power, Heat and Cooling Production System Integrating Gas Turbine and Absorption Cooling - Ali Eivazi; Mohammad Shafiey Dehaj (Journal of Heat and Mass Transfer Research)
In this research, a combined cooling system of heating and electricity is proposed and a complete thermodynamic analysis is presented. The system includes a gas turbine, a heat cooling system, a cogeneration system and a hot water heat exchanger. The basis of the work is that by using the recovery of waste gases in the gas turbine can be generated by a steam turbine and, with the help of an absorption chiller, can recover the waste heat in the steam turbine and provide the required cooling. The cogeneration system saves energy consumption, and reduces environmental pollution. In this study, we have tried to increase the economic justification of using the cogeneration system under study by using up-to-date cost functions. The energy efficiency and exergy efficiency of the studied system are 20 and 21%, respectively, which is a reasonable amount. The results of the economic analysis show that with a total cost of $ 93.56 per second and a total investment and maintenance cost of $ 1732 per second, the proposed system is highly economical and profitable in practice. This may provide a new way to increase the efficiency and effectiveness of thermodynamic performance of cogeneration systems.